The Natural Cycle: WHY Economic Fluctuations are Inevitable. A Schumpeterian Extension of the Austrian Business Cycle Theory - Ferlito, Carmelo (Journal of Reviews on Global Economics, 2014)
The conventional version of Austrian business cycle theory focuses on a temporary imbalance between natural and monetary rates of interest. When, because of the role of monetary authorities in defining the monetary rate, the two values are in a situation of imbalance, the resulting expansion stage is followed by a recession. On the other hand, if instead the expansive phase arises without any interference by monetary authorities but through re-adaptation of the productive structure to a modified structure of temporal preferences, a period of sustainable growth begins that will not be followed by a crisis. The purpose of this essay is to demonstrate, on the other hand, that because of profit-expectations and the combined action of Schumpeterian elements (imitations-speculations and the â€˜creation of money’ by banks), even a so-called â€˜sustainable’ boom will be affected by a liquidation and settling crisis. What distinguishes the latter situation from the conventional case of imbalance between monetary and natural rates is not the onset or otherwise of a crisis but, rather, its intensity and duration. We will define as natural an economic cycle characterised by a stage of expansion considered to be â€˜sustainable’ in the Austrian theory but followed by an inevitable readjustment crisis.